Habitat suitability for Dickcissels (Spiza americana) during spring and fall migration: A species distribution modeling approach - Glass, Alex; Eichholz, Michael W.; Brown, Jason L. (Frontiers in Ecology and Evolution, 2023)
Migratory songbirds have experienced consistent population declines over the past half-century. An important, though often overlooked, contributor to these declines is the loss and degradation of stopover areas during migration, which are critical for allowing migrants to rest and refuel, and arrive in good condition at breeding and nonbreeding grounds. Here, we used publicly available eBird occurrence data to build species distribution models examining habitat suitability of the Dickcissel, a grassland-associated neotropical migrant, during spring and fall migration. Our models included variables representing land cover type, climate, and net primary productivity. Land cover variables were consistently better predictors of Dickcissel occurrence than climate or net primary productivity, suggesting that land cover type has a stronger impact on stopover habitat suitability than environmental factors. During spring migration, Dickcissel occurrence probability decreased with shrubland cover and precipitation seasonality. During fall migration, occurrence probability increased with proximity to water and human development, and decreased with increasing net primary productivity. We detected positive associations during both spring and fall with annual mean temperature and temperature seasonality, and a negative association with forest cover. Surprisingly, our models detected no strong associations with grassland or agriculture, despite the importance of these habitat types for Dickcissels during the breeding and nonbreeding seasons. Ultimately, our results suggest that Dickcissels exhibit greater flexibility when selecting stopover sites compared to breeding or nonbreeding areas, although their avoidance of forest and shrubland may indicate that they will be negatively impacted by further woody encroachment into open habitats across their migratory routes.